2020
DOI: 10.3389/fnhum.2020.00214
|View full text |Cite
|
Sign up to set email alerts
|

Neural Dynamics of Cognitive Control in Various Types of Incongruence

Abstract: Conflict-control is a core function of cognitive control. Although numerous studies have considered cognitive control to be domain-general, the shared and distinct brain responses to different types of incongruence or conflict remain unclear. Using a hybrid flanker task, the present study explored the temporal dynamics of brain activation to three types of incongruence: flanker interference, rule-based response switch (ruleswitch), and action-based response switch (response-alternation). The results showed tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 103 publications
2
15
0
Order By: Relevance
“…In the rare‐change context, a response‐repeat benefit existed (Grzyb & Hübner, 2012, 2013; Mayr & Kliegl, 2003; Meiran et al., 2000; for a review, Altmann, 2011). By contrast, in the frequent‐change context, no response‐repeat benefit occurred, but rather a response‐switch cost (West et al., 2009; Xie et al., 2020). Therefore, the RT of task‐repeat trials would be slower in the frequent‐change context but faster in the rare‐change context, resulting in a smaller switch cost in the former than in the latter.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the rare‐change context, a response‐repeat benefit existed (Grzyb & Hübner, 2012, 2013; Mayr & Kliegl, 2003; Meiran et al., 2000; for a review, Altmann, 2011). By contrast, in the frequent‐change context, no response‐repeat benefit occurred, but rather a response‐switch cost (West et al., 2009; Xie et al., 2020). Therefore, the RT of task‐repeat trials would be slower in the frequent‐change context but faster in the rare‐change context, resulting in a smaller switch cost in the former than in the latter.…”
Section: Introductionmentioning
confidence: 99%
“…This would be associated with the changing N2 amplitudes. That is, N2 amplitudes are expected to increase in the frequent‐change context because N2 is sensitive to the level of cognitive control (Clayson & Larson, 2013; Folstein & Van Petten, 2008; Han et al., 2018) involved in processes of conflict monitoring (Botvinick et al., 2001; Van Veen & Carter, 2002a; Whitehead et al., 2017; Yeung & Cohen, 2006), conflict adaption (Blais et al., 2016; Clayson & Larson, 2011; Forster et al., 2011; Whitehead et al., 2017), and effector switching (West et al., 2009; Xie et al., 2020). Based on studies on the transfer of control settings, the increased cognitive control might transfer to the following task‐switch trials, resulting in larger N2 of task‐switch trials in the frequent‐change context than in the rare‐change context.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, pursuant to previous literature on the P300 there are also P300 latency shifts reported. Peak latencies were found to be delayed for incongruent compared to congruent stimuli, in particular in flanker tasks [ 35 , 37 , 123 ]. Such a timing pattern resembles that of reaction times for incongruent and congruent stimuli and thus suggests a reflection of stimulus evaluation time.…”
Section: Discussionmentioning
confidence: 99%
“…By means of ERPs, we were able to investigate fast event-related electrophysiological correlates of inhibitory processes with respect to congruent and incongruent trials during a flanker task. In healthy subjects, an increased N200 amplitude (a negative-going deflection peaking around 200–400 ms post stimulus onset and maximal over fronto-central sites) for incongruent in contrast to congruent trials resembling a stronger degree of conflict was found [ 33 , 34 , 35 , 36 , 37 ]. Thus, the N200 component is assumed to reflect the activity of a conflict-monitoring mechanism [ 38 ].…”
Section: Introductionmentioning
confidence: 99%